Quinoa extruded snacks with probiotics: Physicochemical and sensory properties - Muñoz Pabon, Karen Sofia; Hoyos Concha, José Luis; Solanilla Duque, José Fernando (Frontiers in Sustainable Food Systems, 2022)
The consumption of probiotic foods has grown rapidly, and these are generally found in dairy matrices where their growth is favored. Therefore, this study aimed to develop a new probiotic snack made from quinoa and added with spore-forming probiotic bacteria in two concentrations of 0.3 and 0.35%. The probiotic was added by spraying, after the extrusion process, together with salt and oil, at 70°C under dry conditions. Bacterial viability, resistance to simulated gastric juice, physical, chemical, and sensory tests were then evaluated during 120 days of storage at room temperature (20°C) and compared to a controlled snack without probiotic. The probiotic Bacillus coagulans was tested for the molecular identification and inhibition of pathogenic bacteria. Viability assessment was remained above 107 CFU/g of snacks. The intestinal tract simulation resistance test showed a viability of 70%. The physicochemical and sensory properties evaluated had no significant changes during storage time compared to control snack. The results of the taxonomic analysis indicate that the analyzed strain has, on average, 98% identity in 98% of its length belonging to Bacillus coagulans and Bacillus badius species. The probiotic showed inhibition against pathogenic bacteria. The new snack with probiotic is stable during storage.